Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/txd.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP3A5 Status on the Clinical and Financial Outcomes Among African American Kidney Transplant Recipients

Abstract: Background. Pharmacogenetic profiling of transplant recipients demonstrates that the marked variation in the metabolism of immunosuppressive medications, particularly tacrolimus, is related to genetic variants. Patients of African ancestry are less likely to carry loss-of-function (LoF) variants in the CYP3A5 gene and therefore retain a rapid metabolism phenotype and higher clearance of tacrolimus. Patients with this rapid metabolism typically require higher dosing to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…As the number of troughs measured and dose changes made increases, resource utilization from laboratory, phlebotomy, pharmacy, and nursing may be increased in an already resource limited setting. We did not evaluate the cost of these resources, but in a recent study, total first year Medicare reimbursement differed by CYP3A5 phenotype where EM had greater spending (p = 0.003) compared to IM 28 . A recent study showed that de novo DSA development was more likely to occur in CYP3A5 expressors (EM or IMs) than nonexpressors (PM) (19% vs. 10%, p = .02) and that expressors experienced more antibody mediated rejection and lower survival rates than non‐expressors 29 .…”
Section: Discussionmentioning
confidence: 99%
“…As the number of troughs measured and dose changes made increases, resource utilization from laboratory, phlebotomy, pharmacy, and nursing may be increased in an already resource limited setting. We did not evaluate the cost of these resources, but in a recent study, total first year Medicare reimbursement differed by CYP3A5 phenotype where EM had greater spending (p = 0.003) compared to IM 28 . A recent study showed that de novo DSA development was more likely to occur in CYP3A5 expressors (EM or IMs) than nonexpressors (PM) (19% vs. 10%, p = .02) and that expressors experienced more antibody mediated rejection and lower survival rates than non‐expressors 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this range of genetic profiles among AA patients contributes to the higher incidence of acute rejection and reduced allograft survival observed in AA KTx recipients. 10,[17][18][19][20] Given the disproportionate potential for harm among AA transplant recipients, the Deterioration of Kidney Allograft Function (DeKAF) genomics study group developed a genotype-guided tacrolimus dosing equation specifically geared toward the genotypes prevalent among AAs. 21 With the narrow therapeutic window (initial trough goal 8-12 ng/mL) and the known variability in tacrolimus metabolism, an effective model that predicts tacrolimus clearance and dose would allow clinicians to achieve therapeutic tacrolimus troughs in less time and with fewer dose adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, AA KTx recipients have a broader range of potential alleles and subsequently high variability in metabolism phenotypes. It has been shown that this range of genetic profiles among AA patients contributes to the higher incidence of acute rejection and reduced allograft survival observed in AA KTx recipients 10,17–20 …”
Section: Introductionmentioning
confidence: 99%